Group Qigong for Adolescent Inpatients with Anorexia Nervosa: Incentives and Barriers. - Juliette Gueguen; Marie-Aude Piot; Massimiliano Orri; Andrea Gutierre; Jocelyne Le Moan; Sylvie Berthoz; Bruno Falissard; Nathalie Godart (PLoS ONE)
Background Qigong is a mind-body intervention focusing on interoceptive awareness that appears to be a promising approach in anorexia nervosa (AN). In 2008, as part of our multidimensional treatment program for adolescent inpatients with AN, we began a weekly qigong workshop that turned out to be popular among our adolescent patients. Moreover psychiatrists perceived clinical benefits that deserved further exploration. Methods and findings A qualitative study therefore sought to obtain a deeper understanding of how young patients with severe AN experience qigong and to determine the incentives and barriers to adherence to qigong, to understanding its meaning, and to applying it in other contexts. Data were collected through 16 individual semi-structured face-to-face interviews and analyzed with the interpretative phenomenological analysis method. Eleven themes emerged from the analysis, categorized in 3 superordinate themes describing the incentives and barriers related to the patients themselves (individual dimension), to others (relational dimension), and to the setting (organizational dimension). Individual dimensions associated with AN (such as excessive exercise and mind-body cleavage) may curb adherence, whereas relational and organizational dimensions appear to provide incentives to join the activity in the first place but may also limit its post-discharge continuation. Once barriers are overcome, patients reported positive effects: satisfaction associated with relaxation and with the experience of mind-body integration. Conclusions Qigong appears to be an interesting therapeutic tool that may potentiate psychotherapy and contribute to the recovery process of patients with AN. Further analysis of the best time window for initiating qigong and of its place in overall management might help to overcome some of the barriers, limit the risks, and maximize its benefits.